Tylna niedokrwienna neuropatia nerwu wzrokowego związana z zabiegiem operacyjnym – patogeneza i charakterystyka kliniczna - Obuchowska, Iwona; Mariak, Zofia (Klinika Oczna / Acta Ophthalmologica Polonica, 2009)
Posterior ischemic optic neuropathy (PION) is an uncommon cause of perioperative visual loss. It has been most frequently reported after spinal surgery and radical neck dissection. This type of PION occurs in the setting of profound hypotension and severe anemia during the perioperative period. The visual loss, which typically presents immediately after surgery, is often bilateral and profound with count fingers vision or worse. The examination findings are consistent with an optic neuropathy, however the optic disc is normal. Diagnosis of PION can be made only after other causes of the optic neuropathy have been excluded. The prognosis for visual recovery is generally poor. Although correction of hemodynamic derangements may be beneficial, no treatment has proven to be effective.